2002
DOI: 10.1034/j.1601-0825.2002.1o787.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the prevalence of HIV‐associated mucosal disease at a dedicated clinic over 7 years

Abstract: These data provide evidence that decreases in the prevalence of oral disease in people with HIV infection can be attributed to the effectiveness of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 14 publications
4
37
2
1
Order By: Relevance
“…[24][25][26] This low prevalence of lesions was confi rmed by the present study. Moreover, the combination therapy has shown to be effective in improving/restoring the quality of life and increasing survival rates of infected patients.…”
Section: Dmft Indexsupporting
confidence: 57%
See 1 more Smart Citation
“…[24][25][26] This low prevalence of lesions was confi rmed by the present study. Moreover, the combination therapy has shown to be effective in improving/restoring the quality of life and increasing survival rates of infected patients.…”
Section: Dmft Indexsupporting
confidence: 57%
“…Birnbaum et al, 24 Greenwood, Zakrzewska and Robinson, 26 Ferreira et al, 31 and Coogan, Greenspan and Challacombe 39 reported changes in the prevalence of oral mucosal lesions following the introduction of ART, including the reduction of the incidence of candidiasis, OHL and KS. A low prevalence of KS was also associated with the use of ART, as reported by Greenspan et al 25 In the present study, 68% of the patients used combination ART for a mean period of 45 months (SD: 37.5 months).…”
Section: Dmft Indexmentioning
confidence: 99%
“…In recent years, the emergence of human immunodeficiency virus infection and the frequent use of immunosuppressant therapy have led to a sharp increase in the incidence of oral infections caused primarily by Candida albicans (10,22,23).…”
Section: Increased Induction Of Interleukin 8 (Il-mentioning
confidence: 99%
“…The low proportions of oral manifestations in this study are likely to have been influenced by use of anti-retroviral treatment which has been made widely since 2004. Petersen (2006 and Greenwood et al, 2002 also emphasized that in most developed countries alike, the availability and consistent use of antiretroviral drugs had dramatic reduction effect on the HIV-related morbidity and mortality. Opportunistic conditions are greatly modified in the era of antiretroviral drugs and increased knowledge of combating the insurgence (Kaste et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction and use of antiretroviral drugs, along with increasing knowledge on HIV and its commonly associated opportunistic infections, the trend of oral manifestations has been greatly modified (Greenwood et al, 2002;Kaste & Bednarsh, 2007;Kisangau et al, 2007). This is regardless the type of medication involved, whether by traditional healing or modern-western (Rudolph et al, 2007).…”
Section: Introductionmentioning
confidence: 99%